PERSONAL SERVICE OF THE DEFENDANT AND APPEALS IN JURY PROCEEDINGS (CIPEEX, 2025)
This paper examines the personal service (intimação pessoal) of the defendant with the decision of indictment (pronúncia) or conviction in Jury Court proceedings and its relation to the filing of appeals, discussing whether the absence of a formal appeal term or of an express inquiry into the defendant’s intent to appeal renders the act void. It aims to determine the legal effects of service, to identify the defence’s burden to file within the statutory deadline, and to indicate when potential defects are merely formal and harmless. Methodologically, it adopts a doctrinal-case-law approach under the Code of Criminal Procedure and courtroom practice, emphasising service as a means to secure effective notice. The findings indicate that personal service is essential to safeguard adversarial proceedings and the right to be heard; however, once service is effected, the State’s duty of notice is fulfilled and, absent prejudice, failure to draw up a formal appeal term or to inquire about the animus to appeal does not invalidate the act; it is for the defendant or defence counsel to file within the legal time-limit. It concludes that nullity analysis must observe the “no nullity without prejudice” principle, preserving legal certainty and procedural celerity without impairing defence guarantees.
Keywords: jury court; personal service